Penanaman Jiwa Entrepreneur Pada Siswa SD di Era Revolusi Industri 4.0 - Friska Dwi Yusantika (JIEES : Journal of Islamic Education at Elementary School, 2021)
This article aims to examine the infuse soul and strengthening of entrepreneurial for students in elementary school through several literature and field studied. The infuse soul of entrepreneurship needs as one part of life skills. Humans must be able to survive in the current era and the next era. Revolusi industry 4.0 has made technology a major tool in human life. The cultivation of entrepreneurial spirit can be carried out through several steps, the integration of entrepreneurship education into the curriculum, learning media, facilities and infrastructure, self-development , co-curricular, local learning, and cultural. The cultivation of entrepreneurial spirit in students does not only involve doing business and entrepreneurship, completing life skills that are oriented to entrepreneurial values.